Pengembangan Instrumen Penilaian Hasil Belajar Yang Mendukung Asesmen Kompetensi Minimum (AKM) bagi Guru Matematika SMP - Isna Rafianti; Ihsanudin Ihsanudin (Jurnal Pengabdian Pada Masyarakat, 2022)
DEVELOPMENT OF LEARNİNG OUTCOMES ASSESSMENT INSTRUMENTS THAT SUPPORT AKM (ASESMEN KOMPETENSI MINIMUM) FOR MİDDLE SCHOOL MATHEMATİCS TEACHERS. The cancellation of the implementation of the UN was realized due to the Covid-19 pandemic that hit in 2020, so it was not possible to carry out the UN with various considerations. Over time, preparations were made to strengthen the AKM and character surveys. The process of developing assessment instruments for junior high school teachers is carried out in a continuous training setting accompanied by experts from universities. Through this service activity for junior high school mathematics teachers, it is possible to collaborate among teachers in various educational units or to develop joint programs for the common good; For example, in professional development. Training and mentoring activities in the development of electronic-based learning outcomes assessment instruments that support AKM have been carried out very well. This is indicated by the results of the response questionnaire of 85% which exceeds the indicators of the success of training and service activities.